2020
DOI: 10.1039/c9ce01651a
|View full text |Cite
|
Sign up to set email alerts
|

Off-stoichiometry effects on the thermoelectric properties of Cu2+δSe (−0.1 ≤δ≤ 0.05) compounds synthesized by a high-pressure and high-temperature method

Abstract: The chemical composition can directly tune the transport properties of Cu2Se liquid-like materials, including the carrier concentration, carrier mobility and superionic feature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…According to Mao’s work, the V c at 750 K is monotonously increased from 0.098 to 0.124 V with the increase of copper deficiency content x from 0 to 0.04 in Cu 2– x Se, which is conducive to stable operation. However, beyond the improved service stability, the excess copper vacancies generate a very high carrier concentration in contrast to the optimal range for excellent ZT. , For example, our works show that ZT is 0.2 at 723 K for x = 0.14 (Cu 1.86 Se), while ZT is 0.15 when x = 0.15 (Cu 1.85 Se), as shown in Figure S1. Herein, it is crucial to balance the decent ZT as well as the large V c in Cu 2– x Se concurrently.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…According to Mao’s work, the V c at 750 K is monotonously increased from 0.098 to 0.124 V with the increase of copper deficiency content x from 0 to 0.04 in Cu 2– x Se, which is conducive to stable operation. However, beyond the improved service stability, the excess copper vacancies generate a very high carrier concentration in contrast to the optimal range for excellent ZT. , For example, our works show that ZT is 0.2 at 723 K for x = 0.14 (Cu 1.86 Se), while ZT is 0.15 when x = 0.15 (Cu 1.85 Se), as shown in Figure S1. Herein, it is crucial to balance the decent ZT as well as the large V c in Cu 2– x Se concurrently.…”
Section: Introductionmentioning
confidence: 75%
“…However, beyond the improved service stability, the excess copper vacancies generate a very high carrier concentration in contrast to the optimal range for excellent ZT. 36,37 For example, our works show that ZT is 0.2 at 723 K for x = 0.14 (Cu 1.86 Se), while ZT is 0.15 when x = 0.15 (Cu 1.85 Se), as shown in Figure S1. Herein, it is crucial to balance the decent ZT as well as the large V c in Cu 2−x Se concurrently.…”
Section: ■ Introductionmentioning
confidence: 78%
“…Nevertheless, the increase in the n of C5− C8 indicated that the alloying of x may have promoted the disorder degree for Cu + ions in Cu 2−x Se, which was similar to the previous report. 44 It can be inferred that the variation of carrier concentration was due to the increasing carrier donors, while the suppressing μ could be attributed to the excess Cu + ion scattering. 44,45 The Seebeck coefficient measured for C8 was ∼35 μVK −1 at 300 K, which linearly increases to ∼102 μVK −1 at 750 K. Figure S5 displays the thermal cycling results of electrical performance for the C8 sample.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For instance, HPHT can induce the production of metastable phase and a change in the band structure, and maintain them at ambient pressure, , thereby influencing the thermoelectric performance . Recently, in terms of experimentation, pure superionic Cu 2 Se bulk was successfully prepared by the HPHT method. , High-pressure processing has been demonstrated to enhance the thermoelectric properties of Cu 2 S by inducing defected microstructures . Moreover, theoretical calculations show that stress can influence the ionic diffusion of ion conductors. , These studies suggest the potential of high-pressure conditions for manipulating the defect structures of materials.…”
Section: Introductionmentioning
confidence: 99%
“…31 Recently, in terms of experimentation, pure superionic Cu 2 Se bulk was successfully prepared by the HPHT method. 32,33 High-pressure processing has been demonstrated to enhance the thermoelectric properties of Cu 2 S by inducing defected microstructures. 34 Moreover, theoretical calculations show that stress can influence the ionic diffusion of ion conductors.…”
Section: Introductionmentioning
confidence: 99%